Penyelesaian Sengketa Konsumen Akibat Perjanjian Baku Dan Klausula Baku Pasca Keberlakuan Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Rachmanto, A. Dwi (UI Scholars Hub, 2018)
After the enactment of Act Number 11 of 2011 concerning the Financial Services Authority (UUOJK), there are 2 (two) of law that regulate the settlement of disputes between business actors and consumers. First, Act Number 8 of 1999 concerning Consumer Protection (UUPK), and the second Act Number 11 of 2011 concerning the Financial Services Authority (UUOJK). This paper will discuss and analyze the resolution of disputes between business actors and consumers after the enactment of Act Number 11 of 2011 concerning the Financial Services Authority by using jurudical normative/dogmatic approach. In the end of the article a number of conclusions were submitted regarding the resolution of consumer disputes based on UUOJK or based on UUPK.